Commentary on Neumann's "Phenomena, Poiēsis, and Performance Profiling: Temporal-Textual Emphasis and Creative Analysis in Turandot at the Metropolitan Opera" - Barolsky, Daniel (Empirical Musicology Review, 2018)
This commentary situates Neumann's research within the existing literature on musicological ontologies of the musical work as well as scholarship on the analysis of performance and recordings. The response focuses on the interdisciplinary strength of the author's method while offering a few caveats about the analytical tools used. Although Neumann ventures into an under-explored territory (i.e. the analysis of operatic voices), I urge the author not to isolate this analysis from other elements of performance, including both visual content and listening experience